Somatic cell hybrid and long-range physical mapping of 11p13 microdissected genomic clones. - Davis, L M (1990)
Microdissection and microcloning of banded human metaphase chromosomes have been used to construct a genomic library of 20,000 clones that is highly enriched for chromosome 11p13 DNA sequences. Clones from this library have been mapped on a panel of human-rodent somatic cell hybrids that divides the region from distal p12 to proximal p14 into seven physical intervals, A total of 1500 clones has been isolated, 250 clones have been characterized, and 58 clones have been mapped. Six of the clones were used to complete a long-range physical map of 7.5 megabases through the region. Two of the clones are localized to the Wilms tumor (WT) region, three are localized to the aniridia (AN2) region, and two are localized to the region between WT and AN2. The library represents DNA sequences spanning a distance of approximately 13 x 10(6) base pairs, with an average density of one clone per 37,000 base pairs.